PROBLEMATIKA NAFKAH MANTAN ISTERI PASCA PERCERAIAN - Aripin, Musa (IAIN Padangsidimpuan, 2018)
Marriage is a sacred thing, that is not just getting legal status, but also various consequences as a result of the engagement ('aqad) to be woven. In a legal marriage, it is mandatory for the husband to provide a living for his wife and submit accordingly. But the reality that occurs in the community, not infrequently husband and wife relations lead to divorce, which then raises new problems, namely the granting of rights in the form of livelihood. The provision of this income is related to the time limit for living, the deadline is the difference between Asghar Ali Engineer and the opinion of the majority of scholars.